PERLINDUNGAN HUKUM BAGI PENJUAL DALAM SISTEM PEMBAYARAN COD MELALUI PLATFORM E-COMMERCE SHOPEE - Noor, Iqbal; Hasyyati, Astrid Amidiaputri (Jurnal Hukum Positum, 2025)
The presence of the e-commerce platform makes it easier for users, but there are problems with the Cash On Delivery payment system so sellers feel disadvantaged. This research aims to determine legal protection for sellers when buyers use the Cash On Delivery payment system via Shopee e-commerce. The research method used by the author is normative juridical with a statutory approach. The research results show that the terms and conditions of the Cash On Delivery payment system have shortcomings which cause buyers to often default. Therefore, the Shopee e-commerce platform needs to evaluate the standard clauses in the terms and conditions of the Cash On Delivery payment method by adding a credit score which aims as a preventive measure, namely an effort to prevent or reduce the risk of default by buyers.